PERTUMBUHAN BENIH LELE MUTIARA (Clarias gariepenus) DI PT. INDOSCO DWI JAYA (FARM FISH BOOSTER CENTRE) SIDOARJO, JAWA TIMUR - Sandy Zakheos Matasina; Sartika Tangguda (Jurnal Akuakultur Rawa Indonesia, 2020)
Mutiara catfish (Clarias gariepenus) is a cross breeding combination of four African catfish strains that have the advantage of relatively complete cultivation performance, one of which has a high growth rate compared to other strains. This study aims to examine the growth of Mutiara catfish seeds so that they can support the availability and sustainability of this super seed. This research is descriptive study with survey method. This research begins with the preparation of the equipments and maintenance media, the maintenance of the broodstock, the spawning process, the egg hatching process, larval rearing and nursery, growth monitoring, and harvesting. Data were analyzed descriptively including weight, length, ADG, and biomass data at the ages of 14, 21, and 28 days. Based on the results of the study, it was seen that there was an increase in weight and length of Mutiara catfish seeds, namely 0.9 grams; 1.6 grams; and 2.8 grams for the weight of seeds, while 0.82 cm; 2.40 cm; and 3.90 cm for the length of the seeds, on the 14th, 21st, and 28th days respectively. Based on these data, it can be seen that the seed growth rate has also increased, namely 0.005 grams; 0.100 grams; and 0.170 grams so that the biomass also increased to 94.27 kg; 167.60 kg; and 277.86 kg. Based on the results of this study, it can be seen that Mutiara catfish seeds have good growth, seen from the ADG and Biomass values which have increased during monitoring. This good growth increase is due to good feeding and good water quality control.